Men, Chronic Pain, and Prescription Pain Medication Use: The Role of Gender Role Beliefs in a Longitudinal Moderated Mediation Model. Issue 12 (10th September 2019) - Daheim, Jacob; Kim, Shin Ye; Neduvelil, Ashley; Nguyen, Nguyen P
Abstract: Objective: Although past research has established that men with chronic pain are more likely to misuse prescription pain medications in a myriad of ways compared with women, little is known about men's medication use in the context of their gender role beliefs. The aim of the present study was to examine the role of men's domestic gender role beliefs on their use of prescription pain medication for chronic pain. Methods: Using a nationally representative data set with 304 men with chronic pain, this study examined a longitudinal moderated mediation model in which pain interference mediates the longitudinal relationship between somatic amplification and prescription pain medication use, with domestic gender role beliefs as a moderator of the aforementioned mediated relationship. Results: Results indicated a significant moderated mediation model in which pain interference fully mediated the relationship between somatic amplification and prescription pain medication use, with men's domestic gender role beliefs moderating this mediated relationship. Specifically, domestic gender role beliefs moderated the relationship between pain interference and prescription pain medication use. Men with higher levels of traditional domestic gender role beliefs strengthened the mediated relationship, contributing to increased prescription pain medication use. Conclusions: These findings suggest that although men's perceptions of somatic stimuli through its perceived interference contribute to their medication use, the extent to which they consume prescription pain medication depends on their beliefs in domestic gender roles during chronic pain.